Key of SDN/NFV development:development and challenge of orchestrator - Peng ZHAO; Xiaodong DUAN (Dianxin kexue)
Network function virtualization (NFV) and software defined networking (SDN) have been widely recognized as the main direction of the development of the next generation telecom network,and as the brain of the future network,orchestrator is the key for the operators to manage the network flexibly and maximize the advantages of new technologies.Firstly,the core position of orchestrator in the next generation network was described,and the technical architecture of orchestrator was introduced.Then,the development of orchestrator in the perspective of standardization and open source were introduced and analyzed.Finally,the relationship between standardization and open source was elaborated,including the integration of orchestrator and OSS,the support of orchestrator for SDN and the idea to realize the intelligent and automatic network operation relying on orchestrator.